Determinant of Capital structure of Nepalese hydropower companies - Rajbanshi, Prem Lal (Pravaha, 2020)
This study examines the effect of profitability, liquidity, size, tangibility and tax shield on capital structure of Nepalese Hydropower Companies. Debt ratio and long term debt to total assets ratio are taken as dependent variable and Profitability, liquidity, size, tangibility and tax shield are as independent variable. The study reveals that tangibility and non debt tax shield are positively influence the total debt where as profitability and liquidity are negatively influence on the total debt decision of the Nepalese Hydropower Companies. The regression coefficients for size are neither consistent nor statistically insignificant in all regression equations indicating that size variable is not the major factor of determinant of total debt as well as long term debt.